2021
DOI: 10.1117/1.jbo.26.10.106501
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of phasor-based analysis for FLIM to evaluate the metabolic and epigenetic impact of HER2 inhibition on squamous cell carcinoma cultures

Abstract: . Significance : Deranged metabolism and dysregulated growth factor signaling are closely associated with abnormal levels of proliferation, a recognized hallmark in tumorigenesis. Fluorescence lifetime imaging microscopy (FLIM) of endogenous nicotinamide adenine dinucleotide (NADH), a key metabolic coenzyme, offers a non-invasive, diagnostic indicator of disease progression, and treatment response. The model-independent phasor analysis approach leverages FLIM to rapidly evaluate cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Similarly to activated macrophages, cancer cells exhibit increased aerobic glycolysis to support proliferation even when oxygen is present, a phenomenon known as the Warburg effect ( Warburg, 1956 ). Autofluorescence lifetime imaging combined with either exponential decay fitting or phasor analysis allows analysis of metabolic phenotypes of cancer cells from FLIM data ( Periasamy et al, 2012 ; Walsh et al, 2014 ; Alam et al, 2017 ; Trinh et al, 2017 ; Pham et al, 2021 ). The phasor plots showed that glycolysis inhibition within MCF7 cells led to a shift towards more bound NADH, while the OXPHOS inhibition stimulated a shift toward more free NADH ( Figure 3G ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to activated macrophages, cancer cells exhibit increased aerobic glycolysis to support proliferation even when oxygen is present, a phenomenon known as the Warburg effect ( Warburg, 1956 ). Autofluorescence lifetime imaging combined with either exponential decay fitting or phasor analysis allows analysis of metabolic phenotypes of cancer cells from FLIM data ( Periasamy et al, 2012 ; Walsh et al, 2014 ; Alam et al, 2017 ; Trinh et al, 2017 ; Pham et al, 2021 ). The phasor plots showed that glycolysis inhibition within MCF7 cells led to a shift towards more bound NADH, while the OXPHOS inhibition stimulated a shift toward more free NADH ( Figure 3G ).…”
Section: Discussionmentioning
confidence: 99%
“…Using FLIM, cells or tissues can be profiled for metabolic state under various conditions such as during glucose shock (see example in Fig. 4d) 117 , infection 125,126 , differentiation [127][128][129][130] , diabetes 131 , drug treatments 117,132 , or in the context of neuro-pathophysiology [133][134][135][136][137] . While examining NADH lifetime can provide valuable insights, imaging conditions especially when fixation or embedding is required need to be carefully evaluated 138 .…”
Section: Tpe Flimmentioning
confidence: 99%
“…The main advantages of phasor analysis are that it provides a visual distribution of the molecular species by clustering pixels with similar decays, it allows for colour mapping of the pixels of the FLIM images, and it is linear in terms of non-interacting molecular species [12,13,17,18]. Phasor analysis of FLIM data is increasingly used in several fields of scientific research [19][20][21][22][23][24] and is particularly used for metabolic imaging with the endogenous biomarkers NAD(P)H and FAD to map their complex autofluorescence distributions in live tissues [5,13,[25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%